2010
DOI: 10.1590/s1679-87592010000300002
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton dynamics in a highly eutrophic estuary in tropical Brazil

Abstract: A B S T R A C TThe port of Recife in northeastern Brazil is an important ecological and social area but little is known about its environmental quality. Observations, sampling and measurements of phytoplankton were performed during spring and neap tides in the dry (January-February, 2005) and rainy (June, 2005) seasons to assess the environmental quality of the port of Recife. The area had chlorophyll-a concentrations ranging from 3.30 to 54.40 mg m -3 , the highest values occurring at low tide during the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
22
0
12

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 31 publications
6
22
0
12
Order By: Relevance
“…This is in agreement with findings for other tropical estuaries in northeastern Brazil where the phytoplankton composition in the rainy season is strongly influenced by the input of freshwater species (SILVA et al, 2009;SANTIAGO et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is in agreement with findings for other tropical estuaries in northeastern Brazil where the phytoplankton composition in the rainy season is strongly influenced by the input of freshwater species (SILVA et al, 2009;SANTIAGO et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the decrease in phytoplankton biomass may be associated with a decrease in the inorganic forms of nitrogen and phosphorus. SANTIAGO et al (2010), who studied the phytoplankton dynamics in a highly eutrophic estuary in northeastern Brazil found that phytoplankton biomass and phosphate concentrations were higher in the dry season. In addition to the influence of point sources, which according to SANTIAGO et al (2010) are responsible for an enhanced eutrophication process in the dry season, the nutrients from runoff events in the rainy period may fuel phytoplankton blooms commonly occurring during the next dry season, when the river discharges decrease significantly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T. musica and G. balticum are tycoplanktonic estuarine diatoms. Both species are present in other tropical estuaries in Brazil (Fujita and Odebrecht 2007;Leão et al 2008;Santiago et al 2010;Masuda et al 2011), while F. capucina is the only tycoplanktonic freshwater form in the present study, commonly reported in other benthonic substrates (Roberts et al 2004;Antoniades et al 2005). The three diatoms mentioned are in water column due to the high dynamism of the estuarine ecosystem, which induces mixture and resuspension of organisms from the bottom (Fujita and Odebrecht 2007).…”
Section: Discussionsupporting
confidence: 54%
“…It is explained by the higher levels of silicate in these waters and thus, its benefits the diatom population (Santiago et al 2010;Borges et al 2012). In addition, our results suggest that the greater occurrence of diatoms in estuaries, comparing with other groups, is due to the different life forms that this population can assume (Table 1).…”
Section: Discussionmentioning
confidence: 99%